2014
DOI: 10.1093/eurpub/cku121
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among immigrants in Europe--a systematic literature review

Abstract: Immigrants 'bring along' their suicide risk, at least for the initial period they spend in the immigration country. Health-care planners and providers need to be aware of this 'imported risks'. However, most immigrant groups do not have an increased suicide risk relative to the local-born population; some may even experience substantially lower risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 33 publications
3
66
0
2
Order By: Relevance
“…However, it has been found that there is substantial heterogeneity of suicide risks among immigrants, relative to those local-born populations of European countries, depending on variations in country-of-birth suicide rates [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that there is substantial heterogeneity of suicide risks among immigrants, relative to those local-born populations of European countries, depending on variations in country-of-birth suicide rates [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Such contradictions and lack of general pattern may be due to a number of varying factors. Somali immigrants in the US believed that suicidal trends did not exist in the Somali community [19]. Furthermore, participants had a difficult time speaking about depression, suicide and emotions openly.…”
Section: Introductionmentioning
confidence: 99%
“…The continuity highlighted by the correlation with suicidality in the migrants' countries of origin may be understood from either a cultural or a genetic perspective. However, the results in this ield are mixed, and while a recent review concluded that, overall, most migrant groups do not have an increased suicide risk relative to the localborn population, with some even experiencing substantially lower risks [15], another one reported higher rates of suicidal behaviors among migrants compared to host populations, which is likely due to diiculties in the acculturation and integration process [3].…”
mentioning
confidence: 78%
“…Furthermore, as already pointed out, migrants may seek psychiatric help only when their distress has reached a severity that requires urgent interventions [55,48]. Lastly, as described in the irst sections of this chapter, the literature on suicidal behaviors in migrants varies, but certain reviews have not found a higher suicide risk in migrants compared to the local-born populations [5,15].…”
Section: Suicidal Behaviorsmentioning
confidence: 93%